Exploration of a Chiral Cobalt Catalyst for Visible‐Light‐Induced Enantioselective Radical Conjugate Addition. (7th August 2019) - Zhang, Kai; Lu, Liang‐Qiu; Jia, Yue; Wang, Ying; Lu, Fu‐Dong; Pan, Fangfang; Xiao, Wen‐Jing
Abstract: Chiral catalysts tolerating photochemical reactions are in great demand for the vast development of visible‐light‐induced asymmetric synthesis. Now, chiral octahedral complexes based on earth‐abundant metal and chiral N4 ligands are reported. One well‐defined chiral Co II ‐complex is shown to be an efficient catalyst in the visible‐light‐induced conjugated addition of enones by alkyl and acyl radicals, providing synthetically valued chiral ketones and 1, 4‐dicarbonyls in 47–>99 % yields with up to 97:3 e.r. Abstract : Chirale oktaedrische Komplexe wurden aus Cobalt‐ und chiralen N4 ‐Liganden hergestellt. Ein strukturell gut definierter Cobaltkomplex erwies sich als effizienter Katalysator in mit sichtbarem Licht induzierten radikalischen konjugierten Additionen. Synthetisch wertvolle chirale Ketone und 1, 4‐Dicarbonyle wurden in 47 bis >99 % Ausbeute (46 Beispiele) mit bis zu 97:3 e.r. erhalten.